Design and Analysis of Three-Degree-of-Freedom Nanopositioning Platform - Hong, Shiwen; Zhu, Haonan; Lv, Zhina; Cui , Liangyu (International Journal of Mechanical and Electrical Engineering, 2025)
To address the issue that the ultra-precision positioning device in the form of piezoelectric ceramic actuated flexible hinge can only be positioned in a single direction, a three-degree-of-freedom nano-positioning platform is proposed. Firstly, the structural designs of the flexible hinge guiding mechanism and the flexible hinge transmission amplification mechanism are conducted, and then the overall structural model of the three-degree-of-freedom nano-positioning platform is designed. Through the static and dynamic modeling, analysis and verification of the bridge amplification mechanism, a theoretical basis is provided for the design of the bridge amplification mechanism. Subsequently, the dynamic platform is simulated, analyzed and verified using ANSYS Workbench to further validate the rationality of the design.